Open partial horizontal laryngectomy using CO2 fiber laser. Issue 8 (8th May 2019) - Crosetti, Erika; Fantini, Marco; Maldi, Elena; Balmativola, Davide; Succo, Giovanni
Abstract: Background: The application of CO2 fiber laser technology to ENT surgery has led to new interesting scenarios, both in endoscopic and in open surgical approaches. Methods: The current video shows three examples of open partial horizontal laryngectomies (OPHLs) performed using CO2 fiber laser for resection procedures. Results: CO2 fiber laser helped the surgeon in improving the accuracy of resection and the quality of surgical margins on specimen. The low thermal damage on tissues resulted in minor postoperative edema and a fast recovery of laryngeal function. Conclusions: In our experience, the application of CO2 fiber laser showed some very useful features for performing OPHLs: a high cutting precision with very low tissue damage, the possibility of delivering energy without touching the organ, a modulable power for the various surgical steps, a very good maneuverability of the fine fiber holder during the procedure allowing the surgeon to "draw" the resection with a great accuracy.